The Portuguese version of Mini-Tinnitus Questionnaire: brief screening test for assessment of tinnitus-induced stress. - Cerejeira, R (2009)
HYPOTHESIS: The Portuguese version of Mini-Tinnitus Questionnaire (Mini-TQ) is as valid as the English version to assess tinnitus-associated distress in the Portuguese-speaking population. BACKGROUND: Tinnitus is a major symptom in ENT practice affecting subjects in all demographic groups. Our objective is to validate a Portuguese version of Mini-TQ (Mini-TQ-pv) to be used in clinical practice and research. METHODS: Mini-TQ-pv was administered to 51 patients with chronic tinnitus. Statistical analysis was done to determine the psychometric properties of the instrument. RESULTS: After double translation, face and content validity were confirmed by high internal consistency (Cronbach alpha = 0.861) and significant correlation between individual items and total score. The questionnaire was easy and quick to administer (2.57 min). CONCLUSION: We provide a suitable Mini-TQ-pv to be used in the assessment of Portuguese-speaking patients with tinnitus